Effects of carob (Ceratonia siliqua L.) pod supplementation of lamb diets on in vitro methane production, digestion, and microbial yield - Kurt, Ozer (Scientific Scholar Llc, 2025)
Enteric fermentation in ruminants produces methane (CH4), which is a major gas that contributes to global warming. The pods of the carob tree, Ceratonia siliqua L., which are abundant in tannins and water-soluble carbohydrates (WSC), could improve microbial protein yield (MPY) and reduce emissions of CH4 without influencing digestion. The effects of carob pod supplementation in lamb diets on CH4 emissions, digestibility, partitioning factor (PF), MPY, and EMPY (efficiency of MPY) were examined in this study. Four iso-caloric and iso-nitrogenous lamb diets (17% crude protein, 2650 kcal/kg dry matter) with differing quantities of carob pods were developed and evaluated using the Menke in vitro gas generation technique. Gas production (GP), CH4 emissions, digestibility, PF, MPY, and EMPY were evaluated during a 24-hour fermentation using buffered rumen fluid from 'Awassi' sheep. The incorporation of carob pods considerably decreased gas and CH4 production (p < 0.001), with a decrease of up to 15% in CH4 emission at higher levels of supplementation. The increase in PF, MPY, and EMPY was accompanied by no change in digestibility. At 30% supplementation, MPY increased by 35.32 mg, while EMPY increased to 31.5% from 23.14% in the control. There was a linear reduction in gas and CH4 emission as the amount of carob supplementation increased. Lamb diets supplemented with 30% carob pods had a 15% decrease in CH4 emissions and an increase in MPY without any change in digestibility. Additional in vivo research is needed to validate the long-term impacts on performance and health, but the results show promise for carob pods to improve ruminant production and decrease emissions of greenhouse gases.
Keywords: Carob pod; CH4 production; Digestibility; Gas production; Lamb diet